2021
DOI: 10.21203/rs.3.rs-582827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Studies On Reduction of Nox Emission of Biodiesel Fuelled Engine Using A Novel Natural Additive

Abstract: The world’s energy demand increases because of increase in human population. The conventional fossil energy resources will be depleted and burning of these conventional fuels increases greenhouse gases and causes global warming. These problems can be overcome using renewable alternative energy resources such as biofuels. In recent years biodiesel is considered as a renewable alternative to the fossil diesel. The utilisation of biodiesel as a fuel in compression ignition engine results in lower CO, HC and Smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Clove oil was investigated as a natural, non-toxic, and sustainable additive for honge oil biodiesel to reduce NOx emissions without altering the engine hardware. Engine tests showed that the addition of clove oil significantly reduced engine NOx emissions and enhanced the oxidation stability of honge oil biodiesel [24]. Clove oil was investigated as a natural, non-toxic, and sustainable additive for honge oil biodiesel to reduce NOx emissions without altering the engine hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Clove oil was investigated as a natural, non-toxic, and sustainable additive for honge oil biodiesel to reduce NOx emissions without altering the engine hardware. Engine tests showed that the addition of clove oil significantly reduced engine NOx emissions and enhanced the oxidation stability of honge oil biodiesel [24]. Clove oil was investigated as a natural, non-toxic, and sustainable additive for honge oil biodiesel to reduce NOx emissions without altering the engine hardware.…”
Section: Introductionmentioning
confidence: 99%